Analisis Faktor-Faktor Penyebab Keterlambatan Proyek Pembangunan RKB Universitas Pasifik Morotai Tahun 2020 - Aminullah Thaib; Anggriyawan Djafar; Alfikram Tanimbar (Jurnal Ilmiah Wahana Pendidikan, 2021)
Every implementation of a construction project, wants to be successful in the implementation of project completion on time. To meet these objectives, three targets must be met, namely the amount of cost (budget) allocated, and the time and quality that must be met. The UNIPAS Lecture Building project for New Classrooms (RKB) is based on work contacts counted 120 calendar days, namely in June Until September 2020, it must have reached 70% for the progress of the work. It's just that in September the progress of the work has only reached 38.29% there has been a delay in work on the project. The main causal factors that have the potential to affect the delay in the completion of the Unipas Campus New Classroom construction project at 0-67% progress carried out by the Implementing Team are (1). Lack of workers, (2). Lack of craftsmen, (3) Inaccurate schedule for material delivery, (4). Financial availability during implementation, (5) Effect of rain on project activities, (6). Material changes in form, function and specifications.